Computers in Cardiology 1994
DOI: 10.1109/cic.1994.470196
|View full text |Cite
|
Sign up to set email alerts
|

Semi-automatic contour detection for volumetric quantification of intracoronary ultrasound

Abstract: Volumetric quantification of the vessel lumen andplaque can be derived @om a sequence of cross-sectional intracoronary ultrasound (ICUS) images. A semi-automatic approach has been developed to detect the contours of the lumen and plaque on a three-dimensional ICUS data set. This approach optimizes the contour aktection algorithm by combining information @om two perpendicular longitudinal views. Preliminary results have shown that this method is able to provide accurate and reproducible measurements of lumen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
1

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 7 publications
0
41
1
1
Order By: Relevance
“…Lumen, stent boundaries, and external elastic membrane were detected using a minimum cost algorithm, and volumetric quantification was performed. 26,27 Percent volume obstruction was calculated as neointimal volume/stent volumeϫ100. The quantitative ultrasound analysis was performed by the same independent core laboratory.…”
Section: Ivus Analysismentioning
confidence: 99%
“…Lumen, stent boundaries, and external elastic membrane were detected using a minimum cost algorithm, and volumetric quantification was performed. 26,27 Percent volume obstruction was calculated as neointimal volume/stent volumeϫ100. The quantitative ultrasound analysis was performed by the same independent core laboratory.…”
Section: Ivus Analysismentioning
confidence: 99%
“…11 This program constructed 2 longitudinal sections from the data set and identified the contours that correspond to the lumen, media, or stent boundaries. Volumetric data were automatically calculated with the following formula: Vϭ⌺ n iϭ1 A i ϫH, where V is volume; A is the area of external elastic membrane, lumen, or plaque in a given cross-sectional ultrasound image; H is slice thickness of the cross section (0.2 mm); and n is the number of digitized cross-sectional images that encompass the volume to be measured.…”
Section: Ivus Image Acquisition Analysis Systemmentioning
confidence: 99%
“…Volumetric data were automatically calculated with the following formula: Vϭ⌺ n iϭ1 A i ϫH, where V is volume; A is the area of external elastic membrane, lumen, or plaque in a given cross-sectional ultrasound image; H is slice thickness of the cross section (0.2 mm); and n is the number of digitized cross-sectional images that encompass the volume to be measured. 11 Offline analyses were performed by 3 independent experienced analysts (K.K., M.C., M.S.) who checked and edited all of the contours of the planar images.…”
Section: Ivus Image Acquisition Analysis Systemmentioning
confidence: 99%
“…16 A Microsoft Windows based contour detection program, developed at the Thoraxcenter, was used for oV line volumetric quantification. 17 Briefly, this program constructed longitudinal sections from the dataset and identified the contours corresponding to the lumen and media boundaries. Intraobserver variability, assessed by analysing IVUS volumetric studies at least three months apart, has been reported-mean (SD): −0.4 (1.1)% and −0.65 (2.66)% in lumen volume, −0.4 (0.6)% and −0.19 (0.67)% in external elastic membrane volume, and −0.3 (1.0)% and −0.95 (2.81)% in plaque volumes using motorised pullback with and without ECG gating, respectively.…”
Section: Three Dimensional Ivus Assessmentmentioning
confidence: 99%